IMPLEMENTATION OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES I N THE CONTROL OF PHYSICAL EDUCATION OF STUDENTS OF SPECIAL MEDICAL GROUPS - Tsjovh, L.; Koryahin, V.; Blavt, O. (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2023)
The relevance of the study is due to the objective need to increase the effectiveness of physical education of students in special medical groups during their training in higher education institutions. A promising direction for solving this problem is the development and practical implementation of new, highly effective control technologies. The purpose of the research: to identify conceptual approaches, the main tasks and mechanisms of the implementation of innovative pedagogical technology for controlling the physical education of students of special medical groups. Material and methods. The basis of the research is the use of a complex of general scientific theoretical methods: analysis, systematization, generalization, theoretical modeling. Results. The basic preconditions and bases of development and introduction of innovative technologies for control of physical education as the process of modernization of the existing control system are analyzed. Formulated conceptual approaches in this process, taking into account the specifics of the contingent of special medical groups. The task is substantiated, the structural components of the mechanism of implementation of innovative control technology are presented and analyzed. In the development of innovative technology, all cycles of diagnostics and management are integrated – from gathering information about the current state of the organism of students to the formation of managerial decisions. The theory of the regulation of cybernetic systems, the main elements of which are programming, screening, correction, is based on the innovative technology of controlling the course of physical education of students. The criterion for the effectiveness of the proposed provisions is the final analysis of the dynamics of the parameters of the psychophysical state of students of special medical groups in the process of their physical education. Conclusions. Integration of innovative technologies, through qualitative changes in the control of physical education of students of special medical groups, leads to an increase in the effectiveness of this process, before quantitative and qualitatively new results. The structure of technology presented in the work allows developing integrated algorithms of activity of subjects of realization of innovations, in order to ensure effective implementation of control of physical education of students of special medical groups, and, thus, increase of efficiency of this process in general.